Variable Optical Buffer Using EIT in Three Level System Based on Semiconductor Conical Quantum Dots - Nooralhuda S.Yaqoob; Sabah M.M. Ameen (Journal of Kufa-Physics, 2020)
A variable semiconductor optical buffer based on the electromagnetically induced transparency (EIT) in a three level conical quantum dot system (CQD) is theoretically investigated. The system is interacting with two (control and signal) laser beams. Signal light with subluminal velocity is possible in such system through the quantum interference effect induced by the control pump field. We investigate the refractive index and absorption spectra of the QD waveguide at different pump levels, which exhibit an optimal pump power for maximum slow-down factor (SDF). The group velocity SDF is theoretically analyzed as a function of the pump intensity at different broadened line widths. The present study is based on the assumption that the medium is homogeneous. In this paper, a SDF as a function of CQD radius was studied. The simulation results indicate that the SDF increases with decreasing CQD radius.